The pragmatic study of metafiction in Preeti Shenoy’s ‘The Secret Wish List’ and ‘It Happens for A Reason’ - D Pandeeswari; A Hariharasudan; Ahdi Hassan (Studies in English Language and Education, 2022)
This study aims to spotlight the postmodern tendency of metafiction in Preeti Shenoy’s selected texts. Metafiction is self-conscious in relation to language, literary form, and storytelling in fiction. This form of fiction accentuates its construct and reminds the readers to be aware of a fictional work. Shenoy is a noteworthy postmodern writer, and her famous novels are ‘The Secret Wish List’ (2012) and ‘It Happens for Reason’ (2014). These two novels exhibit the subject of postmodern metafiction through her writings. In these novels, the protagonists overcome their family doctrines to fulfill their wishes. The method of study adopted the metafiction theories proposed by Mark Currie, Patricia Waugh, and Linda Hutcheon. It highlights Shenoy’s texts that represent the elements of metafiction through the protagonists. Using various theories related to postmodern metafiction, the view of metafiction in the texts is substantiated and explored. The postmodern perspective of metafiction is explored in Shenoy’s texts and analyzed with metafiction theories. The study results are compared and discussed with other studies and contemporary texts concerning metafiction. The findings show that metafiction is applicable in the texts of the two novels by Shenoy. She projects the aspects of metafiction in her works through her writing, especially narration, both fiction and reality.